Survival rates of cervical cancer patients in Sarawak : a single-centre referral study - Melissa Lim, Siaw Han; Shirley Tan, Siang Ning; Izzati, Wan Maharuddin; Pei, Jye Voon; Nur Khairiyah, Abdul Rahim; Xun Ting, Tiong; Cassandra Sheau Mei, Chee; Adam Malik, Ismail; Yolanda, Augustin (BioMed Central Ltd., 2025)
Abstract Background Cervical cancer represents a significant health challenge in Malaysia, especially in the state of Sarawak which records some of the highest incidence rates across the country. This study evaluates the survival rates of cervical cancer patients in Sarawak, focusing on demographic characteristics, disease stage and survival outcomes to inform healthcare strategies. Methods A retrospective case notes review of disease stage, patterns of care and survival outcomes of patients diagnosed with cervical cancer at Sarawak General Hospital between January 2018 to December 2022 was conducted. Kaplan-Meier survival analysis and Cox Regression analysis were performed to assess survival outcomes and factors influencing survival. Results A total of 555 patients were included in this review. The majority of patients were diagnosed between the ages of 40 and 59, with a mean age of 53 years. Ibans comprised the largest subgroup by ethnicity. Only 11.2% of patients were diagnosed with Stage I disease. The majority of patients were diagnosed at advanced stages III and IV. The overall 5-year survival rate was 59.4%. Factors significantly affecting survival included FIGO cancer stage and ethnicity. Conclusions Diagnosis at advanced stages of disease lead to poorer clinical outcomes in cervical cancer patients in Sarawak. This study highlights the critical need for enhanced screening and early diagnosis to improve survival rates amongst cervical cancer patients Sarawak. Efforts should focus on improving cervical health literacy, expanding access to healthcare services and improving the uptake of HPV vaccination and cervical screening particularly in rural communities.